Higher mortality in women after ST-segment elevation myocardial infarction in very young patients - Sadowski, Marcin (Termedia Publishing House, 2013)
INTRODUCTION: Data on mortality in young patients with ST-segment elevation myocardial infarction (STEMI) when compared to older people or regarding therapeutic strategies are contradictory. We investigate the prognosis of women under 40 after STEMI in a prospective nationwide acute coronary syndrome registry. MATERIAL AND METHODS: We analyzed all 527 consecutive men and women (12.3% females) aged from 20 to 40 years (mean 35.7 ±4.5) presenting with STEMI, of all 26035 STEMI patients enrolled. RESULTS: Differences between genders in the major cardiovascular risk factors, clinical presentation, extent of the disease and time to reperfusion were insignificant. The majority of patients (67%) underwent coronary angiography followed by primary percutaneous coronary intervention (PCI) in 79.9% of them. A 92% reperfusion success rate measured by post-procedural TIMI 3 flow was achieved. There were no significant differences between genders in the administration of modern pharmacotherapy both on admission and after discharge from hospital. In-hospital mortality was very low in both genders, but 12-month mortality was significantly higher in women (10.8% vs. 3.0%; p = 0.003). Killip class 3 or 4 on admission (95% CI 19.6-288.4), age per 5-year increase (95% CI 1.01-3.73) and primary PCI (95% CI 0.1-0.93) affected mortality. In patients who underwent reperfusion there was moderately higher mortality in women than in men (7.1% vs. 1.9%; p = 0.046). CONCLUSIONS: Despite little difference in the basic clinical characteristics and the management including a wide use of primary PCI, long-term mortality in women under forty after STEMI is significantly higher than in men.